Geographic variation in ringed seal (Pusa hispida) growth rate and body size - Ferguson, Steven H.; Zhu, Xinhua; Young, Brent G.; Yurkowski, David J.; Thiemann, Gregory W.; Fisk, Aaron T.; Muir, Derek C.G. (Canadian Journal of Zoology, 2018)
We summarize geographical patterns in ringed seal (Pusa hispida (Schreber, 1775)) body length and girth growth using 3012 samples collected by Inuit hunters in the eastern Canadian Arctic from 1990 to 2016. Spatial structure was detected using cluster analysis of environmental variables separating a northern region in the eastern Canadian High Arctic and a southern region in Hudson Bay. The north was characterized by more fast ice, multiyear ice, greater snow depth, colder temperatures, and greater sea-ice concentration in the spring seal breeding season. Hierarchical Bayesian models described length and axillary girth growth of northern seals as slower than in the south, reaching asymptotic size 5–7 years later. Northern females were larger than males (asymptotic length of 149 versus 140 cm, respectively) and both were larger than southern seals (males and females 126 cm). We conclude that environmental variation was best represented by regions rather than latitude, regional body size differences were driven by differential growth rates, and northern ringed seals may be characterized by reverse sexual size dimorphism.